Prevalence and Risk Factors of Brain Infarcts and Associations With Cognitive Performance in Tenants of Marginal Housing. Issue 13 (2nd July 2019) - Zhou, Lily W.; Panenka, William J.; Jones, Andrea A.; Gicas, Kristina M.; Thornton, Allen E.; Heran, Manraj K. S.; Volders, David; Lang, Donna J.; Vertinsky, Alexandra Talia; Rauscher, Alexander; Su, Wayne; Barr, Alasdair M.; et al.
Abstract : Background: Homeless and vulnerably housed individuals are at increased risk for multimorbidity compared with the general population. We assessed prevalence of brain infarcts on neuroimaging and associations with vascular risk factors and cognitive performance in a prospective study of residents living in marginal housing. Methods and Results: Two hundred twenty‐eight participants underwent structured clinical interviews, targeted clinical, laboratory, and neuropsychological assessments, and magnetic resonance imaging with T1, T2 ‐fluid‐attenuated inversion recovery and susceptibility‐weighted images. Subjects underwent cognitive testing to assess premorbid IQ, verbal learning and memory, inhibition, sustained attention, mental flexibility, and decision making. In this sample (mean age 44.0 years [SD 9.4], 77% male), prevalence of conventional vascular risk factors was lower than in the general population apart from tobacco use (94%). Ten‐year Framingham risk for any cardiovascular event was 11.4%±9.2%. Brain infarcts were present in 25/228 (11%). All were ischemic (40% cortical, 56% lacunar, 4% both). Participants with infarcts were older than those without (48.9±9.4 versus 43.4±9.2, P =0.006). In a multivariable regression analysis, only age remained a significant predictor of brain infarcts (odds ratio 1.08, 95% CI1.02–1.14, P =0.004). After controlling for age and education, the presence of infarct was a significant predictor of impaired decision making on the Iowa Gambling Task of decision making (β −28.2, 95% CI −42.7 to −14.1, P <0.001). Conclusions: Prevalence of infarcts on neuroimaging in this disadvantaged, community‐dwelling cohort was much higher than expected for age and was associated with impaired decision making. Further research is needed to identify individuals at highest risk who may benefit from targeted preventative strategies.